Awake at dawn - Hunter, C. C. (A Shadow Falls novel, 2011)
Having settled in at Shadow Falls Camp, a training ground for vampires, werewolves, and other supernatural beings, sixteen-year-old Kylie Galen is eager to discover what her abilities might be, but an interfering ghost and a rogue vampire on a murdering rampage get in the way of her search.